Activation and Purification of ß-Glucocerebrosidase by Exploiting its Transporter LIMP-2 – Implications for Novel Treatment Strategies in Gaucher's and Parkinson's Disease - Dobert, Jan; Bub, Simon; Mächtel, Rebecca; Januliene, Dovile; Steger, Lisa; Regensburger, Martin; Wilfling, Sibylle; Chen, Jia Xuan; Dejung, Mario; Plötz, Sonja; Hehr, Ute; Moeller, Arne; et al. (Advanced Science, 2024)
Genetic variants of GBA1 can cause the lysosomal storage disorder Gaucher disease and are among the highest genetic risk factors for Parkinson's disease (PD). GBA1 encodes the lysosomal enzyme beta-glucocerebrosidase (GCase), which orchestrates the degradation of glucosylceramide (GluCer) in the lysosome. Recent studies have shown that GluCer accelerates α-synuclein aggregation, exposing GCase deficiency as a major risk factor in PD pathology and as a promising target for treatment. This study investigates the interaction of GCase and three disease-associated variants (p.E326K, p.N370S, p.L444P) with their transporter, the lysosomal integral membrane protein 2 (LIMP-2). Overexpression of LIMP-2 in HEK 293T cells boosts lysosomal abundance of wt, E326K, and N370S GCase and increases/rescues enzymatic activity of the wt and E326K variant. Using a novel purification approach, co-purification of untagged wt, E326K, and N370S GCase in complex with His-tagged LIMP-2 from cell supernatant of HEK 293F cells is achieved, confirming functional binding and trafficking for these variants. Furthermore, a single helix in the LIMP-2 ectodomain is exploited to design a lysosome-targeted peptide that enhances lysosomal GCase activity in PD patient-derived and control fibroblasts. These findings reveal LIMP-2 as an allosteric activator of GCase, suggesting a possible therapeutic potential of targeting this interaction.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Gaucher's disease (GD); GCase; LIMP-2; lysosomes; Parkinson's disease (PD); protein purification; β-glucocerebrosidase